The Effect Of Combination Of Perineum Massage With Lavender Aromatherapy On The Degree Of Perineum Rain And Anxiety In Pregnant Mothers 34 Weeks In Mandiri Dyah's Self Practice, Kalasan Sleman - Dyah Febriani Farida (Journal of Applied Health Management and Technology, 2023)
Backgrounds:The prevalence of pregnant women who experience perineal ruptures in Indonesia is still high, age range 25-30 there are 24% cases. This causes anxiety in pregnant women who will give birth. Lavender contains camphor, terpinen-4-ol, linalool, linalyl acetate, beta-ocimene and 1,8-cineole which affects the parasympathetic system so that it has the potential to reduce anxiety. Objectives:To determine the effect of the combination of perineal massage with lavender aromatherapy on the level of perineal rupture and anxiety levels in third pregnant period women at PMB Dyah in 2021. Methods:In this quasi experimental research, pre-post with control group design is implemented. Sampling using saturation sampling technique. PRAQ-R2 is used for research instrument. Data analysis used paired sample t-test, Mann u-Whitney test, Wilcoxon signed rank test and independent t-test. Results:There was a significant difference in the degree of perineal rupture in the experimental group and the control group with p-value = 0.000. There was no significant difference in decreasing anxiety in the experimental group and the control group with p-value 0.176 (fear of giving birth), p-value 0.293 (fear of giving birth to physically/mentally disabled children) p-value 0.070 (worry about appearances). Conclusion: The combination of perineal massage with lavender aromatherapy is not significantly reducing the anxiety of pregnant women during third trimester at PMB Dyah. The combination of perineal massage with lavender aromatherapy more reduces the degree of perineal rupture. Keywords: Perineal Massage; Lavender Aromatherapy; Perineal rupture; Anxiety